Knowledge, Attitude and Skills of Nurses of Delhi towards Adverse Drug Reaction Reporting - P, Amrita; B, Kharbanda (Indian Journal of Pharmacy Practice)
This study was aimed to determine the awareness of nurses of Delhi (India) about Adverse drug reaction (ADR) reporting and their involvement in activities related to pharmacovigilance. A questionnaire was distributed and then collected from the nurses serving in Delhi. The response rate of the survey was 65%. The meaning of term pharmacovigilance was known to 68.27% of nurses. Surprisingly, only 51.92% of nurses understood the correct meaning of the term ADR. None of the nurses knew about the pharmacovigilance centers of India. Only 7.69% nurses knew the reporting centers of Delhi while just 2.88% nurses had their phone number, address. Nurses (93.27%) inform patients about the expected therapeutic effects of the prescribed drugs. Their interaction with the patients regarding side effects was significant. Nurses (90.38 %) said that they report observed ADRs. Majority of the nurses reported the ADRs to the physicians or hospital pharmacy. Nurses felt that, they need not report ADR either because ADR is well known (40.38%) or due to uncertainty about the causal drug (49.04%). About half of the nurses (47.12%) informed that they have existence of set procedure of reporting ADR in their organization. Most (75%) of the nurses did not have ADR reporting forms. Remaining 25% nurses had only localized ADR reporting forms. Thus, we can conclude that nurses are not reporting ADRs to ADR monitoring centers of Central Drugs Standard Control Organization (CDSCO), New Delhi. Education and training is essential for enhancing ADR reporting by nurses to the ADR monitoring centers.
Keywords: ADR; ADR reporting; pharmacovigilance; nurses